Effects of Culture Media and Plant Growth Regulators on In Vitro Growth of Dendrobium pulchellum Roxb. ex Lindl - Singphan, Nootjaree; จันเงิน แพรวพรรณ (King Mongkut’s Agricultural Journal, 2020)
Effects of culture media and plant growth regulators on growth of Dendrobium pulchellum Roxb. ex Lindl in vitro were studied for 84 days after seed germination. The experimental design was Completely Randomized Design (CRD). The results showed that seedling of D. pulchellum Roxb. ex Lindl cultured on 5 culture media which gave percentage of shoot formation, Number of shoots, Number of leave, and height were not significant. While, VW medium supplemented with 2 mg/L BA gave the highest percentage of shoot formation, and Number of shoots. While, VW medium supplemented with 0.5 mg/L Kinetin gave the highest of height of stem, Number of roots, and percentage of root formation, respectively.